Dampak Influencer Marketing terhadap Brand Perception pada product skin care : Studi pada Konsumen Gen Z dikota Bandung - Andi Sukandi; Rachma Waty Fazry; Cut Yusnidar (universitas teuku umar, 2025)
This study aims to analyze the influence of influencer marketing on brand perception of skincare products among Gen Z consumers in Bandung City. The method used in this study is Structural Equation Modeling (SEM) to analyze the relationship between variables and test the proposed hypotheses. Data was collected through a survey involving 200 respondents, consisting of Gen Z consumers who use skincare products and are exposed to influencer marketing on social media. The results showed that influencer marketing has a significant direct influence on Emotion (path coefficient = 0.964), which in turn affects Brand Perception (path coefficient = 0.415). In addition, Trust was found to have a significant direct influence on Brand Perception (path coefficient = 0.551). The moderating effect tested showed that Trust acts as a moderator that strengthens the relationship between Emotion and Brand Perception, albeit with a small effect (path coefficient = 0.028). This research provides valuable insights for marketers and skincare brands to understand how influencer marketing can shape brand perception through emotional influence and the importance of consumer trust in influencers in improving the effectiveness of marketing campaigns. Keywords: Influencer marketing, Brand perception, Gen Z, Structural Equation Modeling,